Oligodeoxynucleotides Can Transiently Up- and Downregulate CHS Gene Expression in Flax by Changing DNA Methylation in a Sequence-Specific Manner - Dzialo, Magdalena; Szopa, Jan; Czuj, Tadeusz; Zuk, Magdalena (Frontiers in Plant Science, 2017)
Chalcone synthase (CHS) has been recognized as an essential enzyme in the phenylpropanoid biosynthesis pathway. Apart from the leading role in the production of phenolic compounds with many valuable biological activities beneficial to biomedicine, CHS is well appreciated in science. Genetic engineering greatly facilitates expanding knowledge on the function and genetics of CHS in plants. The CHS gene is one of the most intensively studied genes in flax. In our study, we investigated engineering of the CHS gene through genetic and epigenetic approaches. Considering the numerous restrictions concerning the application of genetically modified (GM) crops, the main purpose of this research was optimization of the plant's modulation via epigenetics. In our study, plants modified through two methods were compared: a widely popular agrotransformation and a relatively recent oligodeoxynucleotide (ODN) strategy. It was recently highlighted that the ODN technique can be a rapid and time-serving antecedent in quick analysis of gene function before taking vector-mediated transformation. In order to understand the molecular background of epigenetic variation in more detail and evaluate the use of ODNs as a tool for predictable and stable gene engineering, we concentrated on the integration of gene expression and gene-body methylation. The treatment of flax with a series of short oligonucleotides homologous to a different part of CHS gene isoforms revealed that those directed to regulatory gene regions (5′- and 3′-UTR) activated gene expression, directed to non-coding region (introns) caused gen activity reduction, while those homologous to a coding region may have a variable influence on its activity. Gene expression changes were accompanied by changes in its methylation status. However, only certain (CCGG) motifs along the gene sequence were affected. The analyzed DNA motifs of the CHS flax gene are more accessible for methylation when located within a CpG island. The methylation motifs also led to rearrangement of the nucleosome location. The obtained results suggest high specificity of ODN action and establish a potential valuable alternative for improvement of crops.